Steinbeck Squinting - Phil MacMullan:::Creator::::::::::::; Hayman, Lee Richard (collector):::Contributor::::::::::::
A photo of John Steinbeck squinting, possibly at press conference. It appears to be from a Newsweek photo, with the caption underneath reading, "Laurels for Steinbeck."